Sources of Epistemological Obstacles in Understanding Infinity - Krátká, Magdalena (Scientia in educatione, 2013)
The article analyzes three areas of phenomena with which we meet in our effort to identify epistemological obstacles in understanding infinity — Conception of the Objects Existence and related creator’s principle, The Horizon and its Positions, and Knowledge of Finity. Each of the areas is described in detail. Further particular phenomena are illustrated by extracts of experimental interviews. Finally the discussion on these three areas and subsequences in finding specific epistemological obstacles follows.